Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy V; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.

Die zwei Perspektiven des Kundenwerts: Darstellung und Versuch einer Integration - Eggert, Andreas (Kundenwert)

Die zwei Perspektiven des Kundenwerts: Darstellung und Versuch einer Integration - Eggert, Andreas (Kundenwert)

Kundenwert – eine Einführung in die theoretischen und praktischen Herausforderungen der Bewertung von Kundenbeziehungen - Helm, Sabrina; Günter, Bernd; Eggert, Andreas (Kundenwert)

Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.
Keywords: IT-based service; Smart services; Contract renewal; Retention; Customer churn; Free trial

“Service Encounter 2.0”: An investigation into the roles of technology, employees and customers - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Journal of Business Research)
The service encounter – one of the foundational concepts in service research – is fundamentally changing due to rapid evolutions in technology. In this paper, we offer an updated perspective on what we label the “Service Encounter 2.0”. To this end, we develop a conceptual framework that captures the essence of the Service Encounter 2.0 and provides a synthesis of the changing interdependent roles of technology, employees, and customers. We find that technology either augments or substitutes service employees, and can foster network connections. In turn, employees and customers are taking on the role of enabler, innovator, coordinator and differentiator. In addition, we identify critical areas for future research on this important topic.
Keywords: Service encounter; Technology roles; Employee roles; Customer roles; Employee experience; Customer experience

A Nice and Friendly Chat With a Bot: User Perceptions of AI-Based Service Agents - Wünderlich, Nancy; Paluch, Stefanie (Proceedings of the 38th International Conference on Information Systems (ICIS 2017))

How to Design Successful Gamification in Retail: The benefits and Pitfalls of Affordances - Teßmer, Isabel; Olsson, Marcus; Gustafsson, Anders; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)

The Role of Contract Types for Employees’ Public Service Motivation - Grund, Christian; Thommes, Kirsten (Schmalenbach Business Review)

Age diversity and its effects on team performance - Klabuhn, Janny; Thommes, Kirsten (Academy of Management Proceedings)